Synthesis and Crystal Structure of 4,4’-Di-2-pyridyl-2,2’-dithiodipyrimidine (C18H12N6S2) - DONG, HUA-ZE; ZHU, HAI-BIN (Asian Journal of Chemistry, 2010)
A new heterocylic sulfide ligand with molecular formula C18H12N6S2, named as 4,4'-di-2-pyridyl-2,2'-dithiodipyrimidine, was formed by the reaction of 4-pyridin-2-yl-pyrimidine-2-thiol with ferric nitrate. The crystal is monoclinic, space group P21/c with unit cell parameters: a = 11.777 (2) Å, b = 7.2830 (15) Å, c = 20.182 (4) Å, a = 90º, b = 98.832 (4)º, g = 90º, V = 1710.5 (6) Å3, Z = 4, Mr = 376.47, Dc = 1.470 g/cm3, μ = 0.327 mm-1, F(000) = 776, R = 0.0378, wR = 0.0749 for 1820 reflections with I > 2s(I).